2021
DOI: 10.3389/fnana.2021.643287
|View full text |Cite
|
Sign up to set email alerts
|

TRPM4 Expression During Postnatal Developmental of Mouse CA1 Pyramidal Neurons

Abstract: TRPM4 is a non-selective cation channel activated by intracellular calcium and permeable to monovalent cations. This channel participates in the control of neuronal firing, neuronal plasticity, and neuronal death. TRPM4 depolarizes dendritic spines and is critical for the induction of NMDA receptor-dependent long-term potentiation in CA1 pyramidal neurons. Despite its functional importance, no subcellular localization or expression during postnatal development has been described in this area. To examine the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Alternatively, antigenic sites may be masked in tissue, or the antibodies recognize some endogenous protein that is not TRPM4 and is therefore present in both the wild-type and TRPM4-lacking mice. A recent study demonstrated somato-dendritic immunostaining against TRPM4 in CA1 neurons of the hippocampus, however, there was no published validation of these antibodies in Trpm4 –/– tissue 21 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Alternatively, antigenic sites may be masked in tissue, or the antibodies recognize some endogenous protein that is not TRPM4 and is therefore present in both the wild-type and TRPM4-lacking mice. A recent study demonstrated somato-dendritic immunostaining against TRPM4 in CA1 neurons of the hippocampus, however, there was no published validation of these antibodies in Trpm4 –/– tissue 21 .…”
Section: Discussionmentioning
confidence: 97%
“…In the hippocampus, knock-out of TRPM4 impairs theta-burst induced long-term potentiation (LTP) of synaptic transmission 19 and in cerebellar Purkinje cells, both TRPM4 and TRPM5 contribute to, but are not absolutely required for the depolarization-induced slow current 20 . Recently, CA1 pyramidal neurons have been reported to express TRPM4 along the apical dendrites, accompanied by a TRPM4-dependent inward current 21 . TRPM4 may therefore be synaptically activated in CA1 neurons by calcium entering downstream of NMDA and metabotropic glutamate receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic expression of TRPM4 protein may also be related to this time‐dependent cardiac alteration. In mouse CA1 pyramidal neurons the expression of TRPM4 has been shown to increase after birth (Riquelme et al, 2021 ), while it decreases with age in urinary bladder smooth muscle cells (Maxwell et al, 2021 ). Additionally, a cyclic expression of TRPM4 has been shown in female vomeronasal neurons due to the ovarian sex hormone cycle (Eckstein et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…TRPM4 can contribute to the persistent firing pattern of murine thalamic reticular neurons [105]. In murine CA1 pyramidal neurons, TRPM4 was only expressed on the soma at birth and its expression extended during postnatal development from the soma to the apical dendrites but not to the axon initial segment [106]. A TRPM4-like current was active at the resting membrane potential from birth and increased during development, but 10 µM 9-phenanthrol-induced current inhibition hyperpolarized the membrane potential only at later stages.…”
Section: The Proposed Role Of Trpm4 In Various Other Neuronal Functionmentioning
confidence: 99%